النفس الإنسانية عند فخر الدين الرازي = Jiwa manusia apabila Fakhr al-Din al-Razi (The human soul based on the opinion of Fakhr al-Din al-Razi) - El-Bahluol Mohammed Hussein Salem; Mohd Nasir Omar; Ahmad Sunawari Long; Mudasir Rosder (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2012)
Human soul is the mystery of God's creation and His divine verse in the slaves, it is the source of knowledge and different information that is endless, it is also the source of self-evident ideas, but in the same time, it is ambiguous and vague, there are different views on the issue of soul, there are those who differentiate between the soul and the spirit, and from there the view that saw they one thing, even in previous religions and ancient philosophies and primitive beliefs, we find the belief that the self is the object which represents the part of the human rational, and despite the different naming for this wise object between these different doctrines and schools of thought, however the emphasis is on the body more than the soul, perhaps because the body is the concrete physical material, while the soul is the mysterious and invisible part of human, so the sense of its existence needs to exercise a major effort to identify and address it, therefore we can access and get knowledge of it and its illness, so that we may cure these diseases and direct it to the right path of guidance. This paper clarify the meaning of soul, which is commissioned for responsible activities, through which tends to the right and better ethics after the process of accounting, purifying and direction, to emphasize that there is moral philosophy in Islam, and not as the Westerners that it is a philosophy of Greek written in Arabic, to reach out to this result the analytical descriptive method and the comparative method, have been used, and arrived at the result that al-Razi came with several evidences to prove the existence of the human soul, al-Razi opposed the Greek ideas of the human soul transience, which is contrary to Islamic faith, the soul in the Islamic religion have the status of eternity which is not transient.